A wearable patch for continuous monitoring of sweat electrolytes during exertion. Issue 17 (31st July 2018) - Alizadeh, Azar; Burns, Andrew; Lenigk, Ralf; Gettings, Rachel; Ashe, Jeffrey; Porter, Adam; McCaul, Margaret; Barrett, Ruairi; Diamond, Dermot; White, Paddy; Skeath, Perry; Tomczak, Melanie
Abstract : Implementation of wearable sweat sensors for continuous measurement of fluid based biochemical markers is an attractive alternative to common, yet intrusive and invasive, practices such as urine or blood analysis. Abstract : Implementation of wearable sweat sensors for continuous measurement of fluid based biomarkers (including electrolytes, metabolites and proteins) is an attractive alternative to common, yet intrusive and invasive, practices such as urine or blood analysis. Recent years have witnessed several key demonstrations of sweat based electrochemical sensing in wearable formats, however, there are still significant challenges and opportunities in this space for clinical acceptance, and thus mass implementation of these devices. For instance, there are inherent challenges in establishing direct correlations between sweat-based and gold-standard plasma-based biomarker concentrations for clinical decision-making. In addition, the wearable sweat monitoring devices themselves may exacerbate these challenges, as they can significantly alter sweat physiology (example, sweat rate and composition). Reported here is the demonstration of a fully integrated, wireless, wearable and flexible sweat sensing device for non-obtrusive and continuous monitoring of electrolytes during moderate to intense exertion as a metric for hydration status. The focus of this work is twofold: 1- design of a conformable fluidics systems to suit conditions of operation for sweat collection (to minimize sensor lag) with rapid removal of sweat from the sensing site (to minimize effects on sweat physiology). 2- integration of Na + and K + ion-selective electrodes (ISEs) with flexible microfluidics and low noise small footprint electronics components to enable wireless, wearable sweat monitoring. While this device is specific to electrolyte analysis during intense perspiration, the lessons in microfluidics and overall system design are likely applicable across a broad range of analytes.